Rice bran and rice bran oil : chemistry, processing and utilization - Cheong, Lingzhi; Xu, Xuebing, 1962- (Academic Press, 2019)
Rice Bran and Rice Bran Oil (RBO) provides much-needed best practices on the science and technology of RBO, including the chemistry, dectection methods, nutrition (including the effect of processing technologies on micronutrients) and applications. RBO contains many nutritional components, including up to 2% oryzanol, tocotrienol, and phytosterols. In addition, the fatty acid composition is well balanced with mainly oleic acid and very little linolenic acid, which allows for versatile uses in frying, cooking, and in formulating oil blends for food uses, especially as a trans-free alternative. Many food industrial sectors are seeking possibilities to use RBO in their products from not only Asia and South America, but also Europe and North America. However, there are many processing, analytical, and nutritional considerations that must be documented in one resource. This volume is perfect for those interested in understanding the many emerging potential uses for this alternative oil. Written by a team of experts from academia and industry, this book is the first of its kind. In addition, it provides an overview of related rice bran products and their development, including: . Rice bran protein . Rice dietary fiber . Dietary rice bran/meal . Rice husk/ash applications . Paddy straw applications . Valued added products, including rice bran wax.